No-Load and Load Tests on 3 Phase Induction Motors used in Irrigation Pumping with Balanced and Unbalanced Supply - Mallikarjun G Hudedmani; Iranna Hiremath; Shruthi Yaligar; Arshadaunnisa Banu S; Meghna P (Journal of Electronic Design Engineering, 2016)
Agriculture is the major ocupation in villages and is backbone of India, where irrigated agriculture sector plays an important role in economic development and poverty alleviation of the nation. About 75% of present population of India obtains its livelyhood from the same. Iirrigation is harnessing of water resources for the crops by using motor pumps. Usually wells, tanks, perennial canal and multipurpose river valley projects are worked out. As electrical motors are very affordable and cheaper they are the usual choice to drive pumps. Due to the variation in supply to the pump motor the expected performance is not achieved and lead to variation in machine parameters. The operation of 3 phase motor on single phase supply leads to negative effects like overheating, insulation failure, torque pulsation, de rating and reduction in efficiency. In spite of these adverse effects on motor and irrigation power supply feeder, it is observed that farmers run their 3 phase motor on reduced voltage condition using capacitor splitter and other such. A study of operation of 3 phase motor on no-load and load is performed with balanced and unbalanced voltage condition. Simulation is performed in MATLAB/SIMULINK package for the comparison and justification.